Effect of D-Ala-Ended Peptidoglycan Precursors on the Immune Regulation of Lactobacillus plantarum Strains - Song, Xin; Li, Fengjiao; Zhang, Mingshu; Xia, Yongjun; Ai, Lianzhong; Wang, Guangqiang (Frontiers in Immunology, 2022)
The resistance of Lactobacillus plantarum to vancomycin depends on its peptidoglycan composition. Vancomycin has poor binding affinity with peptidoglycan precursors ending in D-alanyl-D-lactate (D-Ala-D-Lac) but binds strongly to peptidoglycan precursors ending in D-alanyl-D-alanine (D-Ala-D-Ala), resulting in resistance and sensitivity, respectively. The ligase Ddl, which generates D-Ala-D-Lac or D-Ala-D-Ala depsipeptides incorporated into the peptidoglycan precursor chain, is responsible for this specificity. To study the effect of peptidoglycan precursors on immunity, we constructed several strains of L. plantarum expressing the ddl gene of Lactococcus lactis to change their peptidoglycan precursors. The change in the termini of the peptidoglycan precursors was determined by the sensitivity of the strains to vancomycin. The overexpression of ddl increased the susceptibility of the strains to vancomycin. We further explored the regulation of the macrophage inflammatory response pathway by the wild-type and constructed strains, and found that these strains induced the MyD88-dependent TRAF6/MAPK pathway, and the increase in D-Ala L. plantarum peptidoglycan precursors increased the secretion of the inflammatory factors IL-6, IL-1β and TNF-α. These results indicate that D-Ala-ended peptidoglycan precursors play a central role in the variable immunomodulatory ability of L. plantarum.